2006
DOI: 10.3122/jabfm.19.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Addiction to Dextromethorphan Cough Syrup: A Case Report

Abstract: Background: Serious drug abuse and addiction related to dextromethorphan-containing cough preparations has been a problem in the United States since the 1950s, but few physicians are aware of it. Physicians must be alert to the type of substances and quantities used and misused by patients in obtaining a thorough routine history of over-the-counter medication use.Methods: We describe the case of a 66-year-old clerical worker who ingested 4 to 16 oz of dextromethorphan on a regular basis over an 8-year period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 11 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Dextromethorphan, as an over-the-counter medicine, is often rationalized by its users as being safer, easier to obtain, widely accessible and undetected on routine drug screening; furthermore, confirmed dextromethorphan dependence is rarely reported in the literature (Bryner et al, 2006;Desai et al, 2006;Navarro, Perry, & Bobo, 2006;Shin, Lee, Kim, Nabeshima, & Kim, 2008;Logan, Goldfogel, Hamilton, & Kuhlman, 2009). Metabolomics is a newly emerging omics approach to the investigation of metabolic phenotype changes induced by environmental or endogenous factors (Patti, Yanes, & Siuzdak, 2012;Deng et al, 2015aDeng et al, , 2015bWang et al, 2015aWang et al, , 2015bWen et al, 2015Wen et al, , 2016aWen et al, , 2016b.…”
Section: Changes In Metabolitementioning
confidence: 99%
“…Dextromethorphan, as an over-the-counter medicine, is often rationalized by its users as being safer, easier to obtain, widely accessible and undetected on routine drug screening; furthermore, confirmed dextromethorphan dependence is rarely reported in the literature (Bryner et al, 2006;Desai et al, 2006;Navarro, Perry, & Bobo, 2006;Shin, Lee, Kim, Nabeshima, & Kim, 2008;Logan, Goldfogel, Hamilton, & Kuhlman, 2009). Metabolomics is a newly emerging omics approach to the investigation of metabolic phenotype changes induced by environmental or endogenous factors (Patti, Yanes, & Siuzdak, 2012;Deng et al, 2015aDeng et al, , 2015bWang et al, 2015aWang et al, , 2015bWen et al, 2015Wen et al, , 2016aWen et al, , 2016b.…”
Section: Changes In Metabolitementioning
confidence: 99%
“…However, the DM dose for the neuroprotective effect is much higher than the cough suppressant dosage. Clinically, high doses of DM can produce psychotropic effects (Wolfe and Caravati, 1995; Desai et al, 2006). Furthermore, DM has been recognized as the object of drug-seeking behaviour in several countries (Cranston and Yoast, 1999; Chung et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…17 There are reports of DXM causing false positives during the initial screen with most reporting false positives for PCP. 4,[18][19] Desai and colleagues found that a 66-year-old woman who had chronically ingested large amounts of DXM in order to induce euphoria, tested positive for PCP from her urine toxicology screen. 19 It has been suggested that DXM can also cause false positives following the initial screen for opiates due to structural similarities, though according to the literature, no conclusive evidence has supported these claims.…”
mentioning
confidence: 99%
“…4,[18][19] Desai and colleagues found that a 66-year-old woman who had chronically ingested large amounts of DXM in order to induce euphoria, tested positive for PCP from her urine toxicology screen. 19 It has been suggested that DXM can also cause false positives following the initial screen for opiates due to structural similarities, though according to the literature, no conclusive evidence has supported these claims. 17,20 On the contrary, a study by Storrow and colleagues showed that adults who ingested doses of 20 mg and 40 mg did not test positive for opioids.…”
mentioning
confidence: 99%